Answer:
( 0 , 3 )
Explanation:
1. Way one of solving this problem
This equation is in standard form, one must get it to slope-intercept form to find the answer. In other words, one must solve for "y"
3x + 4y = 12
Manipulate the literal equation with inverse operations;
3x + 4y = 12
4y = 12 - 3x
/4 /4
y = -
x + 4
2. Way two of solving this equation
The y-intercept is when this line intercepts the y-axis, so "x" is zero. Substitute "0" in for "x", and solve to find the y-intercept
3x + 4y = 12
x = 0
3 (0) + 4y = 12
0 + 4y = 12
Inverse operations;
4y = 12
/4 /4
y = 3